2020
DOI: 10.1021/acs.chemmater.9b04092
|View full text |Cite
|
Sign up to set email alerts
|

Functional Nanoassemblies with Mirror-Image Chiroptical Properties Templated by a Single Homochiral DNA Strand

Abstract: For the supramolecular chemistry of self-assembly systems, a major goal is to achieve the level of control of the assembly process equal to the capabilities of classical asymmetric organic synthesis, such as high stereospecificity, regiospecificity, and reproducibility. Herein we report the stereoselective porphyrin-driven formation of left- and right-handed, chiral functional supramolecular nanoassemblies with mirror image chiroptical properties templated by a single homochiral ssDNA by changing the cooling r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Nucleic acid based assembly is yet another bioinspired scaffolding technique that has been utilized to direct specific molecular architectures. While oligonucleotides and DNA have been subjected extensively to exciton dynamics and charge transport analyses, ,, DNA based scaffolds have also evolved as a strategy to attain arrays of π-electronic molecules, thereby achieving control over the exciton dynamics and charge transport. ,, Nakamura and co-workers demonstrated the vertical assembly of segregated arrays of noncovalently linked NDI acceptors 57 and DPP donors 58 on a gold substrate with the assistance of oligothymidines (dT n ) (Figure ). Separate oligothymidine based stacks of NDIs (1-dT 40 ) and DPPs (2-dT 40 ) were prepared prior to casting the assembled strands on to the substrate, yielding segregated D–A arrays (1-dT 40 /2-dT 40 ).…”
Section: Homo-sorted Donor–acceptor Arrays: Design Principles and App...mentioning
confidence: 99%
“…Nucleic acid based assembly is yet another bioinspired scaffolding technique that has been utilized to direct specific molecular architectures. While oligonucleotides and DNA have been subjected extensively to exciton dynamics and charge transport analyses, ,, DNA based scaffolds have also evolved as a strategy to attain arrays of π-electronic molecules, thereby achieving control over the exciton dynamics and charge transport. ,, Nakamura and co-workers demonstrated the vertical assembly of segregated arrays of noncovalently linked NDI acceptors 57 and DPP donors 58 on a gold substrate with the assistance of oligothymidines (dT n ) (Figure ). Separate oligothymidine based stacks of NDIs (1-dT 40 ) and DPPs (2-dT 40 ) were prepared prior to casting the assembled strands on to the substrate, yielding segregated D–A arrays (1-dT 40 /2-dT 40 ).…”
Section: Homo-sorted Donor–acceptor Arrays: Design Principles and App...mentioning
confidence: 99%
“…Milan Balaz et al reported that the handedness of an achiral porphyrin derivative (DZnPD) nanoassemblies formed with ss-DNA (T40) as a chiral template depended on the cooling rate, whose handedness comes from the broken symmetry (Figure 2B). [50] The left-handed nanostructures were thermodynamically obtained upon slow cooling (700 mM NaCl and 18% dimethyl sulfoxide (DMSO), 0.25 K/min) while the right-handed ones were kinetically obtained upon fast cooling (24-28% DMSO, ∼20 K/min) in the DZnPD and ss-DNA cosystem. Two types of nanoassemblies displayed a nonmirrored opposite CD signal, which were prepared from ss-DNA template with the same chirality.…”
Section: Biomacromolecules or Polymers Induced Cpamentioning
confidence: 99%
“…Reproduced with permission. [ 50 ] Copyright 2020, American Chemical Society. (C) Structures of two isomers of cage 1 (i.e., CAAA‐1 and AAAA‐1), porphyrin 7, and schematic illustration of the enantioselective supramolecular polymerization of seven catalyzed by CAAA‐1.…”
Section: Chiral Assemblies From Achiral Porphyrins Induced By Chiral ...mentioning
confidence: 99%
“…39,41,61,76 These reports highlight the possibility of using CD spectroscopy both to follow the process, usually showing a decrease of the Cotton effect for the Z isomer 38,58,76 to assign the binding mode of both photoisomers, if they are used as ligands, by the pattern of the ICD signal. 38,39 Furthermore, we and others have reported that the chiral environment provided by DNA can influence the chiroptical properties of organic chromophores [77][78][79][80] as well as the stereochemical outcome of a photoisomerization reaction as shown, for instance, for DNA-binding diarylethenes. 29 The same experiment, however, cannot easily be repeated for azobenzenes, as the E isomer is achiral and the Z(P) and Z(M) enantiomers (interconverting helical conformers, Figure 8A) undergo fast isomerization (racemization) in solution 81 i.e.…”
Section: Compound λππ*(E)mentioning
confidence: 92%